Legislar para prevenir: Seguridad y salud en el teletrabajo post Covid-19 - Espinoza Escobar, Javier H. (2023)
This article focuses on the importance that teleworking will acquire in the post COVID-19 labor reality in Peru. The pandemic revealed a series of legislative shortcomings linked, among other issues, to those related to the safety and health of teleworkers. For this reason, this article proposes the minimum content that should be incorporated by the Peruvian legislation on teleworking must incorporate in order to guarantee the safety and health of teleworkers. In the construction of said minimum content, international experiences on the subject have been taken into account.